Functional group polarity-modulated formation of liquid crystals of amphiphilic cyclodextrins. Issue 12 (13th March 2023) - Che, Austin; Zellman, Carson O.; Sarkar, Diganta; Trudel-Lachance, Simon; Espejo, Jayar; Michaelis, Vladimir K.; Williams, Vance E.; Ling, Chang-Chun
Abstract : Polyesterified amphiphilic β-cyclodextrin derivatives bearing functionalized tetraethylene glycols showed excellent abilities to self-assemble into stable hexagonal columnar mesophases with 1D ion conducting channels. Abstract : Cyclodextrins (CDs) constitute a unique class of d -glucose-based macrocycles that possess a truncated cone-shaped central cavity. They are non-toxic and biodegradable. The presence of pseudo face-to-face symmetry in the native CDs represents a distinctive advantage to design amphiphilic materials capable of self-assembly into liquid crystals. In this work, a new family of amphiphilic β-CD derivatives possessing 14 stearoyl chains (non-polar) and 7 functionalized tetraethylene glycols were synthesized using an improved design and more efficient chemistry, and the synthetic targets showed excellent ability to form stable hexagonal columnar mesophases over wide temperature ranges. We demonstrated that the polarity and sizes of introduced functional groups can further affect the temperature ranges of formed LC phases. Moreover, variable temperature solid-state nuclear magnetic resonance spectroscopy studies of a lithium composite with compound 2 revealed fast local Li-ion exchange processes with very low activation energies, suggesting the benefit of using these materials as potential electrolytes for high ionic conductions. The results from this work can provide guidance for the design of future generations of CD-based LC materials for ion conduction.